2008
DOI: 10.1111/j.1540-6261.2008.01392.x
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Banks in Poor Countries: Theory and Evidence

Abstract: We study how foreign bank penetration affects financial sector development in poor countries. A theoretical model shows that when domestic banks are better than foreign banks at monitoring soft information customers, foreign bank entry may hurt these customers and worsen welfare. The model also predicts that credit to the private sector should be lower in countries with more foreign bank penetration, and that foreign banks should have a less risky loan portfolio. In the empirical section, we test these predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
98
1
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 428 publications
(136 citation statements)
references
References 52 publications
9
98
1
6
Order By: Relevance
“…However, his findings also indicated that the contribution of foreign banks to credit provision for small and medium companies is less than that of domestic banks. Cross-country level evidence of Detragiache et al (2008) also supports the idea that FBP is associated with less credit provision. This evidence is based on 89 low-income countries for the period of 1999-2002. A different finding regarding this issue comes from Clarke et al (2005), who conclude that large foreign banks in Chile and Colombia lent more to small-and medium-sized enterprises than domestic banks.…”
Section: Literature Reviewsupporting
confidence: 57%
See 1 more Smart Citation
“…However, his findings also indicated that the contribution of foreign banks to credit provision for small and medium companies is less than that of domestic banks. Cross-country level evidence of Detragiache et al (2008) also supports the idea that FBP is associated with less credit provision. This evidence is based on 89 low-income countries for the period of 1999-2002. A different finding regarding this issue comes from Clarke et al (2005), who conclude that large foreign banks in Chile and Colombia lent more to small-and medium-sized enterprises than domestic banks.…”
Section: Literature Reviewsupporting
confidence: 57%
“…Although some studies (Bleger -Rozenwurcel 2000; Goldberg et al 2000;Berger et al 2001;Satta 2004;Clarke et al 2005;Clarke 2006;Main 2006;Detragiache et al 2008) compare the credit provision of domestic and overseas banks to the domestic market in a specific country or group of countries, the dynamic relationship between FBP and credit availability has remained unexplored. The findings of Berger et al (2001) reveal that small companies in Argentina have a lesser chance of getting credit from foreign and large banks relative to large companies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Choi, Hasan, 2005] oraz obniżenie częstotli-wości występowania kryzysów [Demirgüç-Kunt, Levine, Min, 1998]. Wielu badaczy wskazywało na pozytywny wpływ ekspansji banków z kapitałem zagranicznym przez wprowadzenie lepszych zasad zarządzania ryzykiem kredytowym [Crystal, Dages, Goldberg, 2001;Detragiache, Tressel, Gupta, 2008]. Stremmel i Zsámboki [2015] wskazują jednak, że banki zagraniczne przyczyniły się do zwiększenia amplitudy wahań w cyklu finansowym.…”
Section: Przegląd Literaturyunclassified
“…Foreign entrants cope with crossborder barriers exacerbating information asymmetries. They tend to lend to transparent borrowers based on hard information and have less incentive to lend to opaque borrowers, because of comparative disadvantages in processing soft information (Berger and Udell 2006;Detragiache et al 2006;Dell'Ariccia and Marquez 2004;Sengupta 2007;Maurer 2008). Encountering competition from out-of-market lenders directs local lenders toward opaque borrowers, where they can create comparative advantages against outside lenders.…”
Section: Introductionmentioning
confidence: 96%